Student Unrest – Its Causes and Remedies - Dr. Shaheen Falki (International Journal of Indian Psychȯlogy, 2022)
“Disobedience is the true foundation of liberty. The obedient must be slaves.” This quote by Henry David Thoreau is apt to understand why this theoretical research is important. Student Unrest is that reality that everyone ignores intentionally until it becomes so big that the whole system is threatened by it. Why are students at unrest? Are their reasons reasonable? What can be done to solve the problem of unrest? Several research papers, newspapers, articles, etc. are studied intensely to find out the real causes of this unrest among students. These causes are then divided into different categories and sub-categories. Finally, remedial measures are formulated which will try to curb this problem which threatens to destroy the future of the whole country as students/youths are considered the light-bearer of any country.